(untitled) (Eurasian Journal of Ecology, 2016)
Results of the study shows that the composition of feed coney Liechtenstein (Eremodipus lichtensteini Vinogr., 1927) there are different bodies of more than 40 species of desert plants. Their number increases from west ( Kyzyl Kum– 30 species) to the east ( South Balkhash – 46 species). Food mixed (seed – leaves). Feed composition varies with the seasons. Before hibernation accumulates subcutaneous and visceral fat. It constitutes about 15 % of body weight. Jerboa Liechtenstein is a minor pest of sandy grassland.